Redescription of Rhinocladius Edwards (Diptera: Chironomidae: Orthocladiinae) - Sæther, O. A.; Andersen, T. (Zootaxa, 2003)
Diagnoses of male and female imagines of the genera Rhinocladius are given. R. culicinus known only as female imago is redescribed. R. longirostris is redescribed as male and female imagines. Parsimony analyses show that Rhinocladius, although keying to Apometriocnemus Sæther in Cranston et al. (1989), most likely belong in the Pseudorthocladius group of genera.